The Influence of Self-Acceptance and Social Support on Infertility Stress in Women Experiencing Infertility at RSAB - Wardani, Rachma Sisca; Sovitriana, Rilla (Dinasti Research & Yayasan Dharma Indonesia Tercinta (DINASTI), 2023)
The desire to have children for married couples is something that is very desirable, but in fact, not all married couples can have children easily. There are some couples who find it easy to have children, and there are also couples who need hard work to have children. One of the reasons for not being able to have children is due to infertility problems. Women who experience infertility tend to have low self-acceptance which has an impact on their psychological condition, one of which is experiencing infertility stress. Infertility stress is pressure felt from the surrounding social environment, marital relationships, as well as physical and mental health due to the condition of infertility. Women who experience infertility related stress really need social support from family, partners and friends. This study aims to examine the influence of self-acceptance and social support on infertility stress in women experiencing infertility at RSAB Jakarta. This research is a quantitative study with a population of women experiencing infertility, age range 20-39 years and a sample of 150 respondents. The results of the study showed that there was a significant influence of self-acceptance and social support on infertility related stress in women experiencing infertility (P<0.001 ; ????2 = 0.515). So it can be concluded that there is an influence of Self-Acceptance and Social Support on infertility stress in women experiencing infertility at RSAB Jakarta.